SIFT-NMI Algorithm for Image Matching - Gang Xu; Chen Ma (2011 International Conference on Control, Automation and Systems Engineering, 2011)
SIFT-NMI algorithm is proposed for image matching based on SIFT (Scale-invariant feature transform) and NMI (Normalized Moment of Intertia) algorithm in this paper. Firstly, the SIFT algorithm is used to obtain the coordinates and vector matrix of the image's feature points. Then, the moment of intertia of the vector is obtained based on NMI algorithm and the pairs of matching features points are determined via setting the threshold. Ultimately, the best pairs of feature points are selected via ant colony. Matlab simulation results show that the SIFT-NMI algorithm overcomes the defects of the SIFT algorithm and NMI algorithm, since SIFT algorithm cannot do quantitative calculation and NMI algorithm cannot calculate affine image; by using SIFT-NMI algorithm we can improve the accuracy and speed of matching.